Electric hysteresis and validity of indirect electrocaloric characterization in antiferroelectric ceramics. (15th July 2022) - Li, Junjie; Su, Xiaopo; Wu, Hong-Hui; Li, Jianting; Qin, Shiqiang; Yin, Ruowei; Liu, Chuanbao; Guo, Dong; Su, Yanjing; Qiao, Lijie; Lookman, Turab; Bai, Yang
Abstract: Antiferroelectric (AFE) materials have garnered considerable attention in electrocaloric (EC) refrigeration owing to the large entropy change accompanying their transitions and the coexistence of positive and negative EC effects. Almost all studies to date of EC response in AFEs have employed the indirect characterization of thermodynamic behavior based on the Maxwell relation, regardless of the significant electric hysteresis behavior of AFEs in unipolar polarization. Herein, using direct isothermal heat flow measurements in the AFE ceramic Pb0.99 Nb0.02 [(Zr0.6 Sn0.4 )0.94 Ti0.06 ]0.98 O3 as the benchmark, we discover the large deviation in carrying out indirect EC characterization on AFEs. The electric hysteresis also results in self-heating due to the asymmetric exothermic and endothermic cyclic response, and can be calculated quantificationally from the hysteresis area of P-E loops. Our work emphasizes the necessity in carrying out direct EC characterization on AFEs, and suggests the importance in designing AFE EC refrigeration materials with low electric hysteresis. Graphical abstract: Image, graphical abstract